Inhibitory effects of Skeletonema costatum on mercury methylation by Geobacter sulfurreducens PCA. (February 2019) - Ding, Ling-Yun; He, Ning-Ning; Yang, Sai; Zhang, Li-Juan; Liang, Peng; Wu, Sheng-Chun; Wong, Ming Hung; Tao, Hu-Chun
Abstract: Algae and mercury (Hg) are ubiquitous in marine environments. In this study, we investigated the effects of a typical marine algae of diatom Skeletonema costatum on Hg methylation by an iron-reducing bacterium of Geobacter sulfurreducens ( G. sulfurreducens ) PCA. In the absence of Skeletonema costatum, the bacterial MeHg production rate maximized at 104.06 ± 11.7 ng L −1 h −1 with a high Hg level, while the highest methylation efficiency was achieved at a low Hg concentration. The existence of Skeletonema costatum greatly inhibited the capability of G. sulfurreducens PCA to methylate Hg. With the increase in algal biomass, there was a significant mitigation of MeHg formation and Hg 0 release, leaving a considerable proportion of immobilized Hg 2+ species (up to 47%) associated with algal cell materials. These results suggest that marine algae are crucial in determining the bioavailability of Hg contaminants and the methylating potential of G. sulfurreducens PCA. Highlights: Marine algae of Skeletonema costatum was insignificant in Hg methylation. G. Sulfurreducens PCA was capable of bacterial methylation of Hg. Bacterial methylation depended on initial Hg level and active algal biomass. Bacterial methylation of Hg was inhibited by Skeletonema costatum. Algal biomass was crucial in determining the distribution and transformation of Hg.